STRATEGY FOR DEVELOPMENT OF TOURISM ATTRACTION AT KAMPUNG ADAT RIMBO TAROK PAUH IX KOTA PADANG - Jihan Aulia Fatin; Feri Ferdian (JELAJAH: Journal of Tourism and Hospitality, 2022)
Kampung Adat Rimbo Tarok Pauh IX is a traditional village tourist attraction with the theme of the Thematic Village of Traditional Village, which was newly established on Friday, October 22, 2021, by the Mayor of Padang Hendri Septa. Kampung Adat Rimbo Tarok Pauh IX has an attraction, namely the Gadang Kajang Padati House. Not only that, Kampung Adat Rimbo Tarok Pauh IX also has other attractions in the arts, namely randai, silek, and bamain rago-rago. The purpose of this study was to describe the internal and external factors of tourist attraction in the Kampung Adat Rimbo Tarok Pauh IX, Padang City, including corn plantations, small stages, and Bamain Rago-rago, as well as formulate a strategy for developing tourism objects in Kampung Adat Rimbo Tarok Pauh IX, Padang city. Data collection techniques were carried out through interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results of this study indicate that the tourism attraction development strategy based on 4A Tourism through a SWOT analysis has strengths, weaknesses, opportunities, and threats in the field of attraction, accessibility, amenity, and ancillary.